Geochemistry of coastal sites affected by submarine groundwater discharge along the Puck Bay, southern Baltic Sea - Cátia Milene Ehlert von Ahn; Beata Szymczycha; Magdalena Diak; Olaf Dellwig; Iris Schmiedinger; Michael Ernst Böttcher (PANGAEA, 2025)
This study aimed to characterize the composition of submarine groundwater discharge at the shoreline of the Puck Bay, southern Baltic Sea. Porewater was sampled at various depths down to 50 cm using push point lances with PE syringes and filtered (0.45 μM, disposable cellulose acetate filters) for analysis of for major and trace metals and selected nutrients by ICP-OES (iCAP, 7400, Duo Thermo Fischer Scientific), dissolved ammonium (NH4+) by QuAAtro Analyzer System, total sulphide with a Specord 40 spectrophotometer (Analytik Jena), dissolved inorganic carbon (DIC) and δ13CDIC with an isotope gas mass spectrometer (MAT 253) coupled to a Gasbench II, and δ18OH2O, and δ2HH2O with a CRDS system (laser cavity-ring-down-spectroscopy, Picarro L2140- I). For radium (Ra) isotopes, 5-10 liters of porewater were transferred into canisters without filtration using a peristaltic pump and filtered through a Mn fiber to extract the Ra. The Ra isotopes (224Ra, 223Ra) were measured within 3 and 10 days using radium delayed coincidence counters (RaDeCC). In addition, seepage meters were used to measure seepage water fluxes and to collect samples for the above-mentioned analyses. Sediment cores were taken, sliced at 2 to 4 cm resolution and analyzed for contents of total carbon, nitrogen, and sulphur using an Elemental Analyzer (Euro Vector EuroEA 3, 052), inorganic carbon using an Elemental Analyzer multi EA (Analytik Jena), and total mercury using a DMA-80 analyzer.
In: Ehlert von Ahn, CM et al. (2025): Geochemistry of coastal sites affected by submarine groundwater discharge along the Puck Bay, southern Baltic Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.981211